2015
DOI: 10.1103/physrevlett.114.098101
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Composition Variation and Underdamped Mechanics near Transmembrane Proteins and Coats

Abstract: We study the effect of transmembrane proteins on the shape, composition and thermodynamic stability of the surrounding membrane. When the coupling between membrane composition and curvature is strong enough the nearby membrane composition and shape both undergo a transition from over-damped to under-damped spatial variation, well before the membrane becomes unstable in the bulk. This transition is associated with a change in the sign of the thermodynamic energy and hence favors the early stages of coat assembl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 69 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…II C specializes for the choice of potentials given by Eqs. (28) when T T c (which is the case for the majority of experiments on lipid membranes at room temperature).…”
Section: A Surfaces Of Constant Curvaturementioning
confidence: 97%
“…II C specializes for the choice of potentials given by Eqs. (28) when T T c (which is the case for the majority of experiments on lipid membranes at room temperature).…”
Section: A Surfaces Of Constant Curvaturementioning
confidence: 97%
“…While the history of hybrid models can be traced back to the early nineties and meanwhile became a well-established field of research in theoretical physics (see, e.g. [17,18,30,33,37,40,48,55,58,60,71,76,77] only to mention a few of a multitude of references) the mathematical and numerical analysis of hybrid models is still in its infancy.…”
mentioning
confidence: 99%
“…In particular, it was suggested that they may stabilize membrane composition fluctuations above T c , fostering ordering around the perturbation cen-ters [13]. Furthermore, direct coupling between membrane composition, spontaneous curvature and protein recruitment was clearly demonstrated theoretically [14][15][16][17][18] and experimentally using membrane tethers [19,20]. In these systems, proteins with hydrophobic mismatch (different length of the hydrophobic core as compared to the lipids [21][22][23][24][25]), attract lipids that fit the spontaneous curvature, thereby building a concave or convex shape to fill in the height mismatch.…”
mentioning
confidence: 97%